We are getting stronger as we stay longer: the influence of place attachment to urban community resilience. Issue 1 (November 2021) - Indayani, M; Trisutomo, S; Ramli, M
Abstract: The increasing number of disasters happening in cities has put the sustainability of urban life at stake. One of the measures to strengthen the community's resilience is by understanding how they got attached to the place they live. However, the findings of the previous research regarding the influence of place attachment to community resilience show dissimilarities. This research aims to further reveal the influence of place attachment to communities' resilience in urban areas with a variety of socio-demographic and social dynamics. The study was conducted to 323 households that have frequently been affected by flood, at an urban-village, Tallo sub district, of Makassar City, Indonesia. With simple linear regression analysis, the aspects of place attachment which are personal, social, physical, and cultural are measured to assess its influence on each of their resilience perceptions. The research revealed that there is a positive influence of place attachment to a communities' resilience. Based on the communities' response, it can be seen that resilience is more likely to be formed by social-community aspects.